Optical genome mapping for structural variation analysis in hematologic malignancies. Issue 7 (20th May 2022) - Smith, Adam C.; Neveling, Kornelia; Kanagal‐Shamanna, Rashmi
Abstract: Optical genome mapping (OGM) is a technology that is rapidly being adopted in clinical genetics laboratories for its ability to detect structural variation (e.g., translocations, inversions, deletions, duplications, etc.) and replace several concurrent standard of care techniques (karyotype, fluorescence in situ hybridization, and chromosomal microarray). OGM can dramatically simplify lab workflow by reducing multiple tests (conventional karyotype, fluorescence in situ hybridization [FISH], and chromosomal microarray) into one test. The superior ability to detect structural variation across the genome removes the need for reflex FISH studies, which can dramatically reduce cost and turnaround time per sample. Parallel studies of OGM versus standard of care testing have demonstrated it can detect and resolve more abnormalities than karyotyping or FISH. However, like many molecular tests that normalize copy number it can have difficulty with non‐diploid karyotypes. This Test of the Month review will summarize how the technique works, review the strengths and weaknesses of OGM compared to standard of care techniques and illustrate how the technique is likely to change front line testing in many hematologic malignancies—including summarizing the clinical utility in acute myeloid leukemia, myelodysplastic syndromes, and B cell acute lymphoblastic leukemia. Abstract : Showing conventional "standard of care" cytogenetics techniques: karyotyping, FISH, and microarray. How these techniques can be replaced by Optical Genome Mapping and how the data will look like for comparison. As an example, a t(8;21)(q22;q22) translocation with the RUNX1::RUNX1T1 fusion is shown.